Peningkatan Hasil Belajar Matematika Melalui Pendekatan Matematika Realistik Pada Pokok Bahasan Pecahan Siswa Kelas IV SDN 151 Kadeppe Kabupaten Enrekang - nurdia, nurdia (STKIP Andi Matappa Pangkep, 2018)
Abstract. This study aims to determine the improvement of mathematics learning outcomes on the subject of fractions through a realistic mathematical approach to fourth grade students of SD Negeri 151 Kadeppe, Enrekang Regency and increase the activeness of students in the learning process through realistic mathematical approaches. The method used is classroom action research with two cycles. The results showed that the results of learning mathematics in the Principles of Fractions of Students in Grade IV of SD Negeri 151 Kadeppe, Enrekang Regency after using a realistic mathematics learning approach had increased. Based on the results of this study the authors recommend to classroom teachers that a realistic mathematical approach can be used as an alternative in implementing mathematics learning in schools and the application of realistic mathematics is needed good planning in order to run effectively.